Effects of an ACT-based online intervention on university students’ psychological flexibility, well-being and study skills - Kämper, Ella; Nina Katajavuori; Henna Asikainen (Journal of University Teaching and Learning Practice, 2025)
Online ACT-based interventions, combining psychological flexibility and study skills training, can enhance university students’ well-being and studying. However, less is known about the factors underlying the positive effects of these interventions. The aim of this study is to examine the effects of an ACT-based online intervention on students’ well-being and study skills. The study aims to deepen our understanding of how the participants experienced the intervention and its different components. The mixed-methods findings show that the intervention improved participants’ study skills, psychological flexibility, and emotional and psychological well-being compared to the control group. The intervention components and exercises based on the psychological flexibility sub-processes were experienced by students as supportive of their well-being and learning in a variety of ways. Students highlighted how reflecting on their values helped them to understand what was important to them in their lives and studies and to see whether their actions were in line with this. Practising self-compassion helped students to accept their feelings and thoughts and reduce self-criticism, and mindful presence helped them to cope with stressful situations. In addition to the reflective exercises, students found peer support a meaningful part of the intervention. The benefits of the course components were influenced by individual differences, and the study provides important insights into the individual factors underlying the benefits of the intervention. Understanding these factors can help tailor targeted interventions to a wide range of students and implementing ACT-based online interventions in higher education curricula can help students in promoting their well-being and studying.